One dimensional engine modeling of single cylinder four stroke engine for different cng injection strategy - Mohd Dzulfahizi, Mohamad Saleh (2012)
A simulation work was conducted to compare the effect performances in the cylinder with different injection strategy using compressed natural gas (CNG). The study was based on one dimensional simulation using GT-POWER software. The dimensioning was made on a motorcycle model FZ150i with single cylinder four-stroke engine. The engine was simulated in variations injection strategy with constant speed 4000 rpm with pre-chamber added. The study is focused on characterization of in cylinder pressure and temperature of performance profile for every injection strategy. The other characteristic that has been observed are emissions of CO and NOx between using compressed natural gas (CNG) with gasoline fuel. The output data are post processed using by the GT-POST software. The analysis of the simulation data showed the improvements in the emissions using compressed natural gas (CNG) where reduction in CO and NOx. The results also are shown that the characteristics in the cylinder pressure and temperature versus crank angle engine with constant speed 4000 rpm using compressed natural gas (CNG) with pre-chamber was added is lower than base gasoline engine.